The Czech Republic and the reality of migrant integration policy in the context of European integration - Bauerová, Helena (Array, 2018)
This study has confirmed that the Czech Republic (CR) is an example of a state whose integration and migration policy is very restrictive. Its integration and migration policies have been influenced mainly by migratory flows, economic crises, and European integration. In terms of Europeanisation, it is obvious that the CR carried out fundamental reform in the area of integration and migration policy under the influence of the EU. The implementation of rules in practice has been inadequate. The Czech Republic has recognised and identified the weaknesses of both policies but has not eliminated these weaknesses in practice. The main weakness lies in the fact that both policies are heavily centralised. Local authorities and NGOs do not have sufficient powers and financial resources; moreover, local authorities have no legal obligation to participate in integration. There is a disparity between regions resulting from the unequal concentration of foreigners. A long-term problem is the cultural resistance of society and the requirement for foreigners to assimilate into mainstream society. The migration crisis has increased state activity in the area of migration and integration policy. This is not a manifestation of Europeanisation, but a defence of state interests.